Diet components as internal indicators in the determination of the apparent digestibility coefficients for Nile tilapia - Silva, Rafael Lopes da; Araújo, Eric Portilho de; Rocha, Mariucha Karina Honório Ribeiro; Damasceno, Flavia Mota; Freitas, Jakeline Marcela Azambuja de; Sartori, Maria Márcia Pereira; Meirelles, Paulo Roberto de Lima; Barros, Margarida Maria; Pezzato, Luiz Edivaldo (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the diet components – crude fiber, neutral detergent fiber, acid detergent fiber, hemicellulose, cellulose, and lignin – as internal indicators in the determination of the apparent digestibility coefficients of dry matter, gross energy, and of the nutrients – crude protein, phosphorus, and amino acids – in Nile tilapia (Oreochromis niloticus). Groups of ten juveniles (80.3±1 g) were randomly distributed in six tanks of 250 L and fed two practical diets, either of a plant-origin diet or of a plant- and animal-origin diet. Both diets were supplemented with 0.1% chromium (III) oxide (Cr2O3). Faeces were collected by the modified Guelph system. The apparent digestibility coefficients were determined by the content difference of the internal indicators, present in the diets and faeces, and compared by Dunnett’s test to those obtained by the use of Cr2O3. Cellulose was effective in the determination of the apparent digestibility of dry matter, energy, and nutrients of both experimental diets; and the acid detergent fiber was effective only for the diet composed exclusively of plant-origin ingredients. The use of crude fiber, neutral detergent fiber, hemicellulose, and lignin as digestibility indicators was inefficient for the analyzed nutrients of both diets. Therefore, cellulose is the most suitable indicator for digestibility evaluation in Nile tilapia.